To solve the system of equations using the substitution method, follow these steps:
You have the following two equations:
- \( y = -3 \)
- \( y = 2x + 1 \)
Since the first equation gives you a value for \( y \), you can substitute \( -3 \) for \( y \) in the second equation.
Substituting \( y = -3 \) into the second equation: \[ -3 = 2x + 1 \]
Now, solve for \( x \):
-
Subtract \( 1 \) from both sides: \[ -3 - 1 = 2x \] \[ -4 = 2x \]
-
Divide both sides by \( 2 \): \[ x = -2 \]
Now that we have both \( x \) and \( y \):
- \( x = -2 \)
- From the first equation, \( y = -3 \)
Thus, the solution to the system of equations is \( (x, y) = (-2, -3) \).